Dungeons & dragons. Honor among thieves [videorecording (Blu-Ray)] - Goldstein, Jonathan (Jonathan M.), 1969-; Daley, John Francis, 1985-; McKay, Chris; Gilio, Michael; Pine, Chris, 1980-; Rodriguez, Michelle; Page, Regé-Jean; Smith, Justice, 1995-; Lillis, Sophia, 2002-; Grant, Hugh; Coleman, Chloe; Head, Daisy, 1991- (Paramount Home Entertainment, 2023)
A charming thief and a band of unlikely adventurers undertake an epic heist to retrieve a lost relic, but things go dangerously awry when they run afoul of the wrong people in this hilarious and action-packed adventure.